Technical notes on balance of payments compilation and analysis: The case of Nigeria - Ubong S. Udoette (CBN Journal of Applied Statistics, 2015)
This paper discusses some technical issues in Balance of Payment compilation and analysis. It summarized major components of the BOP statistics, the various account balances as well as the interrelationship between them and other macroeconomic aggregates. It goes further to discuss data related issues in the compilation of Nigeria's BOP statistics with the aim of providing better insight to future/new compilers, policy and other economic analysts.
Keywords: 330